Pakistan : 2009 Article IV Consultation and First Review Under the Stand-By Arrangement; Staff Report; Staff Statement; Public Information Notice and Press Release on the Executive Board Discussion; and Statement by the Executive Director for Pakistan. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2009)
Pakistan has been facing significant economic difficulties. With sharp increases in oil and food prices, and adverse security developments, Pakistan has experienced a significant widening of the fiscal deficit, owing in large part to increasing energy subsidies and major pressures on its balance of payments. As a result, inflation rose considerably and international reserves declined sharply. Executive Directors have commended the authorities for the progress achieved under the stabilization program. Directors have also welcomed the focus on social protection in the authorities' program.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet